A Novel LncRNA, MuLnc1, Associated With Environmental Stress in Mulberry (Morus multicaulis) - Gai, Ying-Ping; Yuan, Shuo-Shuo; Zhao, Ya-Nan; Zhao, Huai-Ning; Zhang, Hua-Liang; Ji, Xian-Ling (Frontiers in Plant Science, 2018)
Environmental stresses are major constraints that limit the leaf productivity and quality of mulberry. LncRNAs have emerged as important regulators in response to biotic and abiotic stresses in plants. However, the functions and mechanisms of most lncRNAs remain largely unknown. A novel lncRNA designated as MuLnc1 was found to be cleaved by mul-miR3954 and produce secondary siRNAs in a 21 nt phase in mulberry. It was demonstrated that one of the siRNAs produced, si161579, can silence the expression of the calmodulin-like protein gene CML27 of mulberry (MuCML27). When MuCML27 was heterologously expressed in Arabidopsis, the transgenic plants exhibited enhanced resistance to Botrytis cinerea and Pseudomonas syringae pv tomato DC3000. In addition, the transgenic MuCML27-overexpressing Arabidopsis plants are more tolerant to salt and drought stresses. Furthermore, the network of mul-miR3954-MuLnc1-siRNAs-mRNAs was modeled to elucidate the interaction between lncRNAs and sRNAs with mRNAs. All of these, taken together, suggest that MuLnc1 was associated with environmental stress in mulberry and may be considered as a potential genetic improvement target gene of mulberry. The information provided may shed light on the complicated gene expression regulatory mechanisms in mulberry stress responses.